New methods in diagnosis and therapySuccessful transcatheter closure of bilateral multiple coronary arterial fistulae in one session - Bacaksiz, Ahmet; Jafarov, Parviz; Ismailoglu, Ziya; Tasal, Abdurrahman (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Coronary artery fistulae represent the most frequent congenital anomalies of the coronary arteries, but multiple bilateral fistulae are a rare condition. Current therapeutic options for symptomatic patients are percutaneous closure and cardiac surgery. Transcatheter closure of fistulae using coils is preferred as an effective and safe alternative to surgery. Here we report the case of a patient with congenital coronary artery fistulae arising from both the left and right coronary arteries draining individually into the right pulmonary artery treated successfully with a transcatheter approach.